Armed resistance of partisans in 1944–1953 and its suppression in Skapiškis rural district - Staveckaitė-Notari, Ramona (Genocidas ir rezistencija, 2024)
There were similarities and differences between armed resistance activities of partisans that took place in various regions of Lithuania in 1944–1953. Still, irrespective of several regional peculiarities, three main periods of the partisan warfare may be distinguished as characteristic of all Lithuania: 1944–1946 – a period of spontaneous fighting, 1946–1948 – a period of organized fighting and 1949–1953 – the end of partisan warfare. Therefore, if you look closely at armed resistance of partisans and tactics they used in the rural district of Skapiškis, you will see a reduced image of all armed activities against occupants across Lithuania. Like everywhere in Lithuania, in Skapiškis rural district, first platoons featuring great numbers of partisans were formed spontaneously. The partisans here used to apply the tactics of attacking the towns. Therefore, on November the 7th 1944, the town of Skapiškis, the centre of the rural district itself, was assaulted. Like everywhere in Lithuania, in this rural district as well, the very first battles of the partisans brought huge losses – the forces of the People’s Commissariat of Internal Affairs (NKVD) attacked numerous platoons of partisans and frequently destroyed them immediately. The young people from Skapiškis land boycotted mobilization to the Red Army. After the call for legalization appeared, a lot of fighters left the forests and hid they relationship with the partisans. The partisans used to hinder the occupants’ authorities from organizing the local elections. During the second part of fighting, in 1946–1948, the issues of uniting the partisan units and transition to organized fighting became the focus of attention of partisan commanders. At that time, the county of Kupiškis was established and Skapiškis rural district became a part of this county. On May 1st 1947, Algimantas Military District was established, and all partisans of Kupiškis land became subordinate to Šarūnas Special Team of that Military District. The last period of fighting stood out from those above by completing the formation of centralized structures of partisans as well as by their destruction. Refined combinations of agencies, activity of the agents, treacheries, destruction of headquarters and military structures and greatly reduced numbers of partisans were the main causes of defeat of both Skapiškis land partisans and those operating all over Lithuania. It has been estimated that during entire period of partisan warfare (1944–1953), in Skapiškis rural district, 40 partisans, their liaisons and supporters lost their lives.